The Influence of Reproductive Health Education Using Chain Whispering Methods on Knowledge and Attitudes of Young Women - Anjeli, A Maya Rupa; Fatmawati, Lilis; Syaiful, Yuanita; Anggraini, Shilvia (Jurnal Ilmiah Kesehatan, 2023)
Health Education is an activity to create health education that seeks to make young people aware of how to take care of their health, how to avoid or prevent things that are detrimental to their own health, one of the problems of young women is the lack of knowledge of reproductive health. This study aims to determine the effect of reproductive health education using the whisper chain method on the knowledge and attitudes of young women. The design of this research is pre-experimental. The design of this study uses the Pre-test – Post-test Design. The population of all grade VI students is 22 students. The sample of this research was class VI girls at UPT SD NEGERI 60 Gresik. The sampling technique was carried out by purposive sampling with 21 female students who met the inclusion and exclusion criteria as respondents. The independent variable of health education and the dependent variable are the knowledge and attitudes of young women about reproductive health using the chain whisper method. Data was collected using knowledge and attitude questionnaires before and after the provision of reproductive health education. Reproductive health education using the chain whisper method was carried out for 1 time 120 minutes at UPT SD Negeri 60 Gresik, Cerme District, Gresik Regency. Statistical test using the Wilcoxon Test ≤0.05. The results of the research on knowledge of young women before being given reproductive health education (poor) after (good) p=0.001, attitudes of young women before being given reproductive health education (negative) after (positive) p=0.000. This means that there is an influence of reproductive health education using the chain whisper method on the knowledge and attitudes of young women. For this reason, the researchers hope that this research can be used as a form of routine activity to add insight to female students about reproductive health.